Potrayal of Islam and muslims in the talk shows of CNN And BBC - Sargana, Noor Hayat; Wahab, Juliana Abdul (2015)
This study explores the portrayal of Islam and Muslims in the Western mainstream media talk shows, CNN and BBC from January 2012 to December 2012 and draws the required data from their online editions. It is a content analysis of 50 programs focusing on Islam and Muslims from Piers Morgan Live, Fareed Zakaria GPS, HARDtalk and Newsnight. The findings show that rather than economics, religion and war on terror both news channels were more focused in discussing the political shifts and regional transformations of the Muslim world. Mostly the geopolitical issues of Middle East and North Africa (MENA) region were given immense coverage in the discussions and Muslims were framed as politically fanatics. The findings also established that Western media differs from the previous rhetoric by not framing Muslims as terrorists, violent and threat to Western democracy